Association of smoking with myocardial injury and clinical outcome in patients undergoing mechanical reperfusion for ST-elevation myocardial infarction. (13th March 2016) - Reinstadler, Sebastian J.; Eitel, Charlotte; Fuernau, Georg; de Waha, Suzanne; Desch, Steffen; Mende, Meinhard; Metzler, Bernhard; Schuler, Gerhard; Thiele, Holger; Eitel, Ingo
Abstract : Aims There is evidence suggesting a positive effect of cigarette smoking on myocardial tissue reperfusion and clinical outcomes in patients with myocardial infarction ('smoker's paradox'). We aimed to evaluate the relationship of smoking with cardiac magnetic resonance (CMR)-determined myocardial salvage and damage as well as clinical outcomes in patients undergoing primary percutaneous coronary intervention (PPCI) for ST-elevation myocardial infarction (STEMI). Methods and results This multicentre study included 727 consecutive STEMI patients reperfused within 12 h after symptom onset. CMR imaging parameters [area at risk (AAR), infarct size (IS), myocardial salvage index (MSI), and microvascular obstruction (MVO) and intramyocardial haemorrhage (IMH)] were compared according to admission smoking status. Major adverse cardiac event (MACE) rates at 12 months after infarction were compared between groups. Three hundred and thirty-nine (46.6%) patients were current smokers. There was no difference in the extent of AAR [35 (24–47) vs. 37 (27–49) % of left ventricular volume (LV), P = 0.10], IS [16 (8–25) vs. 17 (10–26) %LV, P = 0.21], MSI [53 (29–70) vs. 52 (34–71), P = 0.47], MVO [0 (0–1.7) vs. 0 (0–1.6) %LV, P = 0.91], or in the frequency of IMH (42 vs. 39%, P = 0.58) between smokers and non-smokers. Smokers had lower MACE (3.8 vs. 8.2%, P = 0.01) rates. However, adjustment for differences in baseline risk factors attenuated the association of smoking with MACE markedly (hazard ratio = 0.71, 95% confidence interval 0.36–1.38, P = 0.31). Conclusion Smoking is not associated with PPCI efficacy (myocardial salvage) or irreversible myocardial damage in patients with STEMI. The lower MACE rate of smokers was entirely explained by differences in baseline risk characteristics, thus challenging the existence of a smoker's paradox.